The Unique Realities of Roma Lgbti in Albania - Ramizi, Mirjeta (International Journal of Scientific Research and Management (IJSRM), 2020)
Roma LGBTI inequalities based on ethnicity, race, gender and sexual orientation have an intersectional character and build upon the intersection of these identity variables rather than having an aggregate factorial value, constitutes the major methodological-research question in this study. Understanding social structures, discrimination and disadvantage of LGBTI Roma in Albania involves scientific qualitative methodological tools in order to unveil the diversity, variations, differences and heterogeneity.The lesbian, gay, bisexual, transgender and intersex Roma people in Albania tell complex histories of being, both, present in and excluded from the communities they live in. Being different is a reality and the efforts to feel part of a community, are ongoing and painful. The LGBTI Roma see the world first and foremost from the point of view of race, gender and sexual orientation. The findings show that violence and discrimination against the LGBTI Roma community are a wide-spread phenomenon and manifested in the most severe and traumatic forms.The living stories of LGBTI Roma are rooted in the structural inequalities based on the intersection of sexual orientation, gender and ethnicity. LGBTI Roma in Albania are a “unique reality” which does not correspond and does not represent the reality of a Roma or LGBTI person. The research proves that from the methodological point of view in social sciences an illiterate gay Roma with low incomes is different from a gay illiterate and with low incomes (an illiterate + gay + Roma + low incomes ≠ from a gay + low incomes + illiterate).